Differences in the literacy skills of Danish dyslexic students in two types of higher education programmes. (25th April 2019) - Bønnerup, Katrine H.; Pedersen, Anne Leth; Weed, Ethan; Parrila, Rauno
Abstract : Previous research has treated high‐functioning dyslexic students as a homogeneous group. This study explores the clinical observation that dyslexic students attending university programmes differ from dyslexic students attending tertiary education professional programmes in some aspects of their literacy skills. Four groups, dyslexic university students ( n  = 32), dyslexic students attending professional programmes ( n  = 32), control university students ( n  = 31), and control students from professional programmes ( n  = 30), were assessed on measures of pseudoword reading, phonological choice, vocabulary, reading and spelling of morphologically complex single words, and reading aloud from a syntactically complex text. The results showed that the two dyslexic groups were comparable only on the phonological tasks, the dyslexic university students outperforming the professional programme students in all reading and spelling measures. Controlling vocabulary and number of semesters studied, the difference was no longer significant. Nevertheless, the analyses indicate that phonological deficits underlie the performance of professional programme students with dyslexia across a wide range of tasks, whereas university students with dyslexia may be able to limit the impact of phonological deficits to some extent by relying on some alternative cognitive attributes. Reading experience, orthographic learning, and working memory efficiency are discussed as possible explanations for this pattern of results.